Partially open crack model for leakage pressure analysis of bolted metal-to-metal flange. (August 2015) - Beghini, M.; Bertini, L.; Santus, C.; Guglielmo, A.; Mariotti, G.
Highlights: Fracture Mechanics similitude between partially open crack and flange interface. Weight Function analytical implementation of zero SIF as leakage condition. FE validation on several flange geometries and very accurate correlation. Experimental successful validation of the model leakage pressure prediction. Parametric analysis and geometry optimization guidelines. Abstract: Predicting the leakage condition is of primary importance when designing metal-to-metal flanges. The gap between flange surfaces is regarded as a partially open crack with a zero stress intensity factor, then a model based on fracture mechanics is proposed for predicting leakage pressure. An analytical solution was found, with weight function, considering the condition of crack front at the most internal point of the bolt hole. Finite element and experimental tests validated the effectiveness of the model. In addition, the dependencies on the main flange dimensions were investigated and discussed, providing useful guidelines for optimal flange design.